Macroeconomic analysis and international finance - Kouretas, Georgios P.; Papadopoulos, Athanasios P. (Emerald, 2014)
This volume contains new important research on banking institutions and performance in transition economies, economic growth and inequality and exchange rate economics and international finance. Topics include exchange rate exposure of firms, the relationship between monetary policy and house price shocks, economic interdependence of south-eastern European countries, Chinas exchange rate policy and economic growth, inequality and financial sector. Among the questions answered are : is exchange rate volatility a significant determinant of average firm level exposure? Can we identify shocks that can be interpreted as loose monetary shocks, low inflation shocks, banks credit shocks and house price shocks? What are the main factors driving the relationship between banks and companies in transition economies? Does it matter for forecasting GDP growth whether the economy is in tranquil times or during a period of turbulence? Has economic growth played any role in reducing inequality in South Africa? Are global bilateral investment holdings characterized by strong persistence? And finally, is China's international competitiveness fluctuates in consistency with PPP equilibrium?
Includes index.
Keywords: Macroeconomics.; International finance.; elektronické knihy; electronic books